Chair for the session ”Shipping Finance”, Multinational Finance Society (MFS) Spring 2016 Conference - Tsouknidis, Dimitris (My University, 2026)
Chair for the session ”Shipping Finance”, Multinational Finance Society (MFS) Spring 2016 Conference, Limassol, Cyprus, 22-24 April, 2016.